No Sugar, Please! Tobacco Anthropology and the Merits of Contingent Conceptualisation - Holbraad, Martin (Anthropologica, 2019)
Deploying Fernando Ortiz’s ethnological contrast, in Cuban Counterpoint, between the generality of sugar and the particularity of tobacco, this article argues that the practice of anthropology is best compared to the latter. Anthropology’s constitutive investment in the particulars of ethnography renders it a “science of the contingent” par excellence, inherently averse to necessities and generalisations of all types. With reference to the recent literature on the “ontological turn” in anthropology, I argue that this investment consists above all in the attempt to turn contingent ethnographic materials into equally contingent conceptualisations. Such a procedure, however, is not contrapuntal in its nature. This is because the relationship between ethnography and its conceptualisation is not symmetrical on the horizontal axis in the way counterpoint is. Unlike counterpoint, therefore, it is the basic difference in kind between ethnographic realities and the concepts they generate that makes their relationship in the process of anthropological analysis interesting.